It's difficult to show Gaussian elimination process here. But the answers should be,
x = 1, y = -4 and z = -2
Solve the system of equations using matrices. Use Gaussian elimination with back- substitution.
x+y+z = -5
x-y+3z = -1
4x+y+z = -2
3 answers
Thank you so much , but I'm supposed to show my work :/
x +y + z = -5...i
x - y + 3z = -1...ii
4x + y + z = -2 ...iii
frm (i)
y = -5-x-z ....(iv)
frm (ii)
y = x+3z+1....(v)
frm (iii)
y = -2-4x-z .....(vi)
equate (iv) = (v)
-5-x-z = x + 3z + 1
x+x+3z+z = -5-1
2x+4z = -6 .....(VII)
equate (iv) = (vi)
-5-x-z = -2-4x-z
4x-x-z+z = 5-2
3x = 3
x = 3/3
x = 1
to get z let subt value of x = 1 in (VII) , we have
2x + 4z = -6
2(1) + 4z = -6
4z = -6-2
4z = -8
z = -8/4
z = -2
to get y .. Let subtitute da value of x nd z in equatn (i) , we have
x + y + z = -5
(1) + y + (-2) = -5
1 + y - 2 = -5
y = -5 + 2 - 1
y = -4
so values are :
x = 1
y = -4
z = -2
add me up on facebook if u care
#Tommyjattommy
Am a Nigerian
x - y + 3z = -1...ii
4x + y + z = -2 ...iii
frm (i)
y = -5-x-z ....(iv)
frm (ii)
y = x+3z+1....(v)
frm (iii)
y = -2-4x-z .....(vi)
equate (iv) = (v)
-5-x-z = x + 3z + 1
x+x+3z+z = -5-1
2x+4z = -6 .....(VII)
equate (iv) = (vi)
-5-x-z = -2-4x-z
4x-x-z+z = 5-2
3x = 3
x = 3/3
x = 1
to get z let subt value of x = 1 in (VII) , we have
2x + 4z = -6
2(1) + 4z = -6
4z = -6-2
4z = -8
z = -8/4
z = -2
to get y .. Let subtitute da value of x nd z in equatn (i) , we have
x + y + z = -5
(1) + y + (-2) = -5
1 + y - 2 = -5
y = -5 + 2 - 1
y = -4
so values are :
x = 1
y = -4
z = -2
add me up on facebook if u care
#Tommyjattommy
Am a Nigerian